Isle of Man : Financial Sector Assessment Program Update; Technical Note; Stress Testing; Banking and Insurance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This technical note presents stress testing of banking and insurance on the Isle of Man (IOM). The stress tests for the IOM Financial Sector Assessment Program Update have been designed to yield as comprehensive and detailed a picture as possible within the constraints of the approach and available data. Stress tests have been performed both by individual institutions based on the parameters and scenarios agreed between the authorities and IMF staff, and, at an aggregate level and in many instances, by the authorities themselves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet